Peningkatkan Hasil Belajar PAI Mengunakan Metode Diskusi di SMAN 1 Kecamatan Situjuah Limo Nagari - Linda, Mesra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Religious Education (PAI) through the implementation of the discussion method. This method was chosen because it enhances students’ active participation and makes the learning process more enjoyable and interactive. The subjects of this study were 10 students from class XI F6 at SMAN 1 Situjuah Limo Nagari. This research employed a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. Data were collected through learning outcome tests, observation sheets, and field notes. Data analysis was performed qualitatively descriptively to observe improvements in students’ learning outcomes from cycle to cycle. The results of the study indicate a significant improvement in students’ learning outcomes after implementing the discussion method. In the first cycle, the percentage of students achieving mastery was 70%, with an average score of 73.5. After the second cycle, the mastery percentage increased to 85%, with an average score of 83.5. Additionally, students demonstrated improvements in activeness and collaboration during the learning process. Based on these findings, it can be concluded that the implementation of the discussion method is effective in enhancing students’ learning outcomes in PAI for class XI F6. This method also increases students’ motivation and engagement in the learning process. Therefore, the discussion method is recommended as an interactive learning alternative for Islamic Religious Education.